The Effect of Cinnamon Compress on Reducing Joint Pain in Elderly Patients with Gout Atrhritis at the Elderly Social Home: A Pre-experimental Study - Dani Erlangga; Andre Utama Saputra; Alvian Harisandy; M Ramadhon (Lentera Perawat, 2025)
Joint pain is a common disease in the community of the elderly group. To reduce the pain can be done by the administration of non-pharmacological therapy one of them with cinnamon compresses that aim to reduce the pain, prevent the occurrence of muscle spasms. The purpose of this study was to find out the effect of cinnamon compress on the reduction of joint pain in the elderly suffering from gout arthritis in our hope social home Palembang in 2024. This researcher used a pre-experimental design, by using the One Group pre-test Post-test design approach. The sampling used total sampling with a total of 30 respondents. The instrument in this study used SOP (Standard Operating Procedures) administration of cinnamon compresses and Observation sheet using Numerical Rating Scale (NRS). By using the Paried T-Test statistical test. The results of the study found that there was a change in joint pain before giving cinnamon compress obtained mean 5.37 while after giving cinnamon compress therapy obtained mean 2.73. based on the pared T-test obtained a p value of 0.000 < 0.05, this shows that joint pain in the elderly in our social home hope palembang. By giving cinnamon compresses can have an impact and more effective on the scale of moderate joint pain. From the results of this study it is expected that cinnamon compress therapy can be used as one of the alternative ways in reducing joint pain in the elderly.